Book Review: Beyond Caring Labour to Provisioning Work - Tyyskä, Vappu (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
Sheila M. Neysmith, Marge Reitsma-Street, Stephanie Baker Collins, and Elaine Porter. Toronto: University of Toronto Press, 2012